Các yếu tố ảnh hưởng đến cảm xúc của giáo viên tiếng Anh trong các mối quan hệ nghề nghiệp tại các trung tâm ngoại ngữ tư nhân - Trần, Khắc Duy; Ngô, Huỳnh Hồng Nga (Tạp chí Giáo dục, 2025)
Teachers’ emotions play an important role in shaping their professional lives, influencing their development, teaching effectiveness, well-being, and career commitment. While the emotions of language teachers have been widely investigated globally, research remains limited within the context of Vietnamese private language centers. Based on Hargreaves’ emotional geographies theory, this study employed a narrative approach to investigate the factors influencing the emotions of English as a foreign language (EFL) teachers in their professional relationships. Data was collected from narrative frames of 30 EFL teachers and semi-structured interviews with 3 selected teachers. The findings indicated that EFL teachers experienced both positive and negative emotions in professional relationships. These emotions were influenced by limitations of online teaching environments, professional purposes gap, generational gaps, hierarchical power structures, and differences in professional norms. The research highlights the complex and dynamic nature of teachers’ emotions and offers valuable insights for educational managers and teachers to optimize the professional environment, particularly in private foreign language centers in Vietnam.